Efektifitas Media Interaktif Berbasis Articulate Storyline dalam Meningkatkan Hasil Belajar Siswa Kelas IV pada Materi Mengenal Peta - Raisa Berlian; Rieskha Tri Adilah. Em; Yesika Novita Rahmi (Kartika: Jurnal Studi Keislaman, 2026)
Students learning outcomes in science and social science (IPAS) learning remain a concern, particularly in the topic of map recognition, which involves visual concepts and requires instructional media that can enhance student engagement. The limited use of instructional media has resulted in less interactive learning processes, contributing to low learning outcomes. This study aimed to analyze the effectiveness of interactive learning media developed using Articulate Storyline in improving the learning outcomes of fourth-grade elementary school students on the topic of map recognition. This study employed a quantitative approach using a one-group pretest-posttest design. The participants consisted of 24 fourth-grade students at SDIT Al-Manar Pekanbaru. Data were collected through pretests and posttests and analyzed using the Normalized Gain (N-Gain) test to determine the improvement in students' learning outcomes. The findings revealed that the mean score increased from 58.75 on the pretest to 93.75 on the posttest, while the learning mastery rate improved from 33.3% to 91.6%. Furthermore, the average N-Gain score was 0.90, which falls into the high category. These findings indicate that the Articulate Storyline-based interactive learning media is effective in improving students' learning outcomes and can serve as an innovative instructional medium for IPAS learning in elementary schools